ANALISIS KUALITAS MAKANAN PADA SAAT BREAKFASTDI THE ALIGA HOTEL PADANG - ivony tresia (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2018)
Thisdstudy originated from the resultsiofiprevious studies where there were problems regarding the process of managing the procurement of perishable goods that did not have written procedures, the quality requirements of the material written and standardized in the hotel. To continue the problem where there are still problems related to food quality at breakfast at The Aliga Hotel Padang. This study aims to analyze food quality at breakfast at The Aliga Hotel Padang. This type of studyiisiquantitativepdescriptive. The population in this study were guests who stayed and breakfast at The Aliga Hotel Padang. The sampling technique used is purposive sampling. The totaliofisamplesiin this study amounted to 91 people. Data collection techniques were carried out by distributing questionnaires (questionnaires) using the Liker scale that has been tested for validity and reliability. Thenitheidata wereianalysisithrough data tabulation and descriptive data using percentages. Based on the research that has been done, the results obtained that the quality of food at breakfast at The Aliga Hotel Padang is in the category of enough with a percentage of 45.05%. It is recommended for other researchers to continue research on the quantity of food. Keywords: Food Quality, Breakfast